THE EFFECTIVENESS OF POAC IMPLEMENTATION IN CUCUMBER PRODUCTION MANAGEMENT FOR FARMERS AT THE MANDIRI SEJAHTERA FARMERS COOPERATIVE SUKARAJA DISTRICT SUKABUMI REGENCY: EFEKTIVITAS PENERAPAN POAC DALAM PENGELOLAANPRODUKSI MENTIMUN PADA PETANI DI KOPERASI TANI MANDIRISEJAHTERA KECAMATAN SUKARAJA KABUPATEN SUKABUMI - Muhammad Irham Alfariji; Ashrul Tsani; Ema Hilma Meilani (ROCE : Jurnal Pertanian Terapan, 2026)
This study aims to analyze the effectiveness of implementing POAC (Planning, Organizing, Actuating,Controlling) management functions in managing cucumber (Cucumis sativus L.) production by farmers in the Mandiri Sejahtera Farmers Group, Sukaraja District, Sukabumi Regency. A descriptive qualitative research method was used, with purposive sampling, to select five farmer respondents. Data were collected through in-depth interviews, observations, and questionnaires, and then analyzed qualitatively using the POAC framework. The results indicate that farmers have inherently applied POAC principles adaptively and pragmatically, albeit with varying degrees of formality. Planning is adjusted to agroclimatic conditions and varietal preferences, resource organization is efficient, implementation follows standard cultivation procedures, and control is responsive to field conditions. The effectiveness of POAC implementation has been proven to support cucumber productivity in highland areas where rainfall is a dominant factor. The main constraints are dependence on rainwater and informal recording, but there is potential for improvement through a more structured recording system and diversification of water sources. This study adds to the understanding of POAC management adaptation at the small-scale farmer level.